Echoes of the Anthropocene, Through the Keyhole of Law Consciousness - Kapartziani, Chrysoula (European Scientific Journal, ESJ, 2024)
The concept of the “Anthropocene”, that is, the interconnection between human activity and what was once called the natural environment, becomes a direct response to the radical changes in climate and ecosystems that have transformed the ecology of our planet and may have led us to the pandemic crisis. Human agency, which is always regulated through legal instruments, becomes the focal point of everything in the planet. Law is a great reservoir of emotionally important social symbols as well as a powerful instrument. Thus, crucial is the understanding of the ways by which our legal environmental rules have come to be formed. This understanding of the law, society, environment and citizen’s place within, is described by the term “legal consciousness”. Furthermore, law is a set of conceptual categories and schemes that help construct, communicate, and interpret social and cultural relations. Taking under consideration that the Anthropocene is also a state of consciousness and environmental awareness goes hand in hand with legal consciousness, now is the time that we can create a new legal culture. How legal schemes were and are present in the words, actions, and interpretations of ordinary citizens until now? What is the role, if any, of educational system and media? Do we need to rewrite legal terminology, redefine our legal values and frameworks to depict the interconnection between nature and human activity? What are the best ways for the communication of the contemporary legal rules (e.g., the rights of nature, etc.)? Should they be produced through open participatory processes? What do we learn from environmental history examples?